Study of the Characterization of Amorphous Alloy Co87Nb46B15 - Nascimento, Luciano; Melnyk, Anastasiia (Orbital: The Electronic Journal of Chemistry, 2017)
This paper presents a discussion of the processing and characterization of alloy Co87Nb46B15 produced by rapid solidification, in which characterization techniques such as X-Ray Diffraction (XRD), scanning electron microscopy and Spectroscopy Dispersion Energy (SEM / EDS) and magnetic properties were used, with the study of hysteresis curve. Several researches were done about nanocrystalline materials, especially cobalt-base alloys, because of their thermodynamic stability, characterization and processing. Amorphous alloys have a structure of ultrafine, homogeneous grains with small crystal clusters in amorphous phase.DOI: http://dx.doi.org/10.17807/orbital.v9i1.889